2020
DOI: 10.3892/etm.2020.8535
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory marker alteration in response to systemic therapies in psoriasis

Abstract: Substantial research has focused on the presence of biomarkers involved in both the pathogenesis of psoriasis and its comorbidities. The identification of these biomarkers has a crucial role in establishing the diagnosis and prognosis, in understanding the physiopathological mechanism and in determining the therapeutic response. The aim of this study was to emphasize the alteration in inflammatory markers in response to systemic therapies in psoriasis. Evolution of inflammatory marker alteration was studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Recent research regarding cardiovascular risk in psoriasis suggests that chronic inflammation may be considered a component of the metabolic syndrome in which activation of type 1 T helper cells is present. The upregulation of type 1 T helper cells was observed in metabolic syndrome in correlation with several cytokines such as IL-6 and TNFα (29)(30)(31). IL-6 is a pleiotropic cytokine with a critical defense role in acute inflammatory response during infections and posttraumatic tissue injuries, promoting the synthesis of acute phase proteins including reactive C protein, amyloid A and fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research regarding cardiovascular risk in psoriasis suggests that chronic inflammation may be considered a component of the metabolic syndrome in which activation of type 1 T helper cells is present. The upregulation of type 1 T helper cells was observed in metabolic syndrome in correlation with several cytokines such as IL-6 and TNFα (29)(30)(31). IL-6 is a pleiotropic cytokine with a critical defense role in acute inflammatory response during infections and posttraumatic tissue injuries, promoting the synthesis of acute phase proteins including reactive C protein, amyloid A and fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…A biological treatment for psoriasis (Etanercept) was shown to decrease the previously increased CRP serum levels in patients suffering from moderate and severe psoriasis 15 . A recent study reported that treating psoriasis with both methotrexate and biological therapy showed a significant decrease in the patients serum levels of CRP, ESR and fibrinogen 16 …”
Section: Discussionmentioning
confidence: 99%
“…15 A recent study reported that treating psoriasis with both methotrexate and biological therapy showed a significant decrease in the patients serum levels of CRP, ESR and fibrinogen. 16 Psoriasis severity and its correlation with inflammatory markers in response to treatment was evaluated by Kanelleas et al who found F I G U R E 2 Abdomen and forearm of a male patient before, A, and after, B, 36 sessions of NB-UVB showing moderate decrease in infiltration and scaling, and mild decrease in erythema that CRP serum levels diminished posttreatment (P < .001) and identified a relationship between PASI scores and CRP. 17 Another study reported a direct correlation between psoriasis severity and CRP serum levels that were decreased significantly following phototherapy sessions.…”
Section: F I G U R E 1 Treatment Protocol For Phototherapy Using Nb-umentioning
confidence: 99%
“…Regarding biological therapy, based on the mechanism of action, it is divided into: T lymphocyte modulating agents (alefacept, efalizumab), TNF-α inhibitors (infliximab, adalimumab, etanercept), IL-12/IL-23 inhibitors (ustekinumab, briakinumab, guselkumab, risankizumab), and IL-17A inhibitors (ixekizumab, secukinumab) (1). The use of biological therapy significantly reduces inflammatory activity in psoriasis, this being demonstrated in various studies by measuring inflammation markers CRP, ESR and fibrinogen (28). It has recently been shown that biologic therapy prevents the formation and even reduces the growth of atheroma plaque (23,29,30).…”
Section: Effects Of Systemic Therapymentioning
confidence: 94%